Primers Used in This Study. - Jianhua Liao (1393228) (2025)
The growing prevalence of methicillin-resistant Staphylococcus aureus (MRSA) infections, coupled with the increasing resistance to existing antibiotics, underscores the critical need for novel therapeutic approaches to combat this pathogen. In this study, the role of yqhG, a conserved gene encoding a periplasmic protein, in MRSA virulence and stress adaptation was investigated. yqhG deletion in MRSA significantly attenuated virulence in a murine infection model, leading to reduced bacterial burden in infected organs and improved host survival. In vitro, the yqhG mutant exhibited impaired membrane integrity, reduced motility, and increased sensitivity to oxidative stress, but did not affect biofilm formation. These defects were fully restored upon genetic complementation. These findings highlight the critical role of yqhG in maintaining MRSA’s ability to withstand host-imposed stresses, suggesting that yqhG is a key determinant of MRSA pathogenesis. The study provides new insights into the stress-defense mechanisms employed by MRSA and underscores yqhG as a potential target for therapeutic strategies aimed at combating MRSA infections.